EFEKTIFITAS MEDIA CEKER-CEKER UNTUK MENINGKATKAN KEMAMPUAN OPERASI HITUNG BAGI ANAK TUNAGRAHITA RINGAN - Lia Zahara, Tarmansyah, Elsa Efrina (Universitas Negeri Padang, 2013)
The research was motivated by the problems that researchers in the school discovered that a student's with mental retardation DII C SLB Al Islah Padang who have difficulty operating in reduction numbers 1-10. The ability of researchers want to improve students' skills in the school of reduction operations numbers 1-10 with the use ceker-ceker media reduction surgery 1-10. This research uses experimental approach in the form of single subjeck research (single subject research), with ABA design and data analysis techniques using visual analysis chart. This research is the subject of mental retardation children. assessment in this study is to measure the percentage of students' ability to perform subtraction with numbers 1-10 using a ceker-ceker media. From the results of the study can be seen in the baseline condition conducted in eight sessions, students were only able to get a 0% on the first meeting up to eight, the graph indicates stability. After being given treatment in the intervention condition students' abilities in performing, the reduction operation improving. Data numbers 1-10 shows the stability of the meeting until the seventeenth meeting of twenty with the highest score 100%, with the results of the students were able to do all the problems. then the baseline condition with no treatment is given, the data demonstrate the stability of the meeting to twenty-one to twenty-four meeting with the highest score of 100%, with the results of the students were able.to do all the problems. then the baseline condition with no treatment is given, the data demonstrate the stability of the meeting to twenty-one to twenty-four meeting with the highest score of 100%. the problems. It can be concluded that the use of media ceker-ceker reduction operations can improve the ability of numbers 1-10 mild mental retardation children DII class C SLB Al-Ishlaah Across Padang. Suggested to the principal and teachers to make the results of this study as a reference for the development of learnig proccess in school.